(untitled) (Revista Científica Integrada, 2023)
Aim: to characterize the effluent generated by a textile industry, specifically jeans, and to propose different techniques for its treatment, such as compaction by gravity and dewatering by centrifugation. Methods: Intervention study, carried out in 2022, in Ribeirão Preto, São Paulo. The physical-chemical characterization of the effluent was carried out, analyzing its main parameters and, after analyzing the data, it was noted the need for adequate treatment of this effluent. Subsequently, consolidation (sedimentation) and centrifugation tests were carried out with the addition of different chemical conditions, aiming at reducing the values of turbidity, color, and organic carbon of the effluent. Results: In the consolidation tests, the natural polymer Tanfloc stood out in relation to the others, with removal of 88% of turbidity, 78% of apparent color, 81% of true color and 55% of total organic carbon. In the centrifugation tests, the natural polymer Tanfloc also stood out, reaching a turbidity removal of 97%, 83% of apparent color, 75% of true color and 87% of total organic carbon. Conclusions: it is necessary to adequately treat the effluent from the textile industry and, for the effluent analyzed, the treatments by sedimentation and centrifugation proved to be efficient in reducing the parameters of turbidity, color, and organic carbon.